PENGGUNAAN TEKNIK DESENSITISASI SISTEMATIS UNTUK MENGURANGI KECEMASAN SISWA PADA SAAT PRESENTASI - Ferlysta Ayu Febbyanti; Giyono Giyono; Diah Utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study was to determine whether students' anxiety during a presentation can be reduced by desensitization techniques systematically for class X students of SMK Negeri 1 Metro in the academic year 2012/2013. The problem In this study is that students who experience anxiety at the time of presentation. The problem in this research is